Production and consumption aspects of biogas in cattle farming businesses of Ukraine - Doronin, Andriy; Rybchak, Vitaliy (Turystyka i Rozwój Regionalny, 2015)
Production and consumption aspects of biogas at farm enterprises of Ukraine were identified. Preconditions of negative changes in cattle farming were studied. The research done made it possible to evaluate production efficiency of both beef and alternative fuel – biogas – at farm enterprises. A polynomial model, which describes potential of biogas production in the years of 1990–2013 and envisages further increase of this indicator, was developed. It has been established that biogas production and consumption from cattle substrates at farm enterprises will allow producing ecologically clean alternative fuel, ensuring food safety, creating new jobs, increasing business profits, reducing import fuel dependence. The research results can help solve practical problems of farm enterprises in cattle farming and in agrarian business in general.